Impossible Poetics, or Aesopic Language in Relation to Semiotics and Literary Sociology - Satkauskytė, Dalia (Colloquia, 2016)
The author of this article discusses the tradition of studying Aesopic language and comes to the conclusion that textual analysis of this phenomenon and descriptions of its poetics and semantic mechanisms are inadequate if they do not take the social dimension into account. She recommends seeing Aesopic language as a sociopoetic form whose poetics are inseparable from conditions of reception, and whose aesthetics are rooted in a historically defined communication situation and dependent on the conditions of social production. Choosing this concept of Aesopic langauge allows the author to reveal a wide circle of questions that are connected to how literature functions under conditions of political censorship: how the social context becomes incorporated into the semantics of Aesopic language; what effect literary tradition and its use in indirect political criticism have on how Aesopic language functions in society; what were the conditions of artistic communication during the Soviet period and what these say about the structure of the literary field; the effect of the political field; the status of the artist; the role of literature under the conditions of the communist regime, and so on. In her exploration of these questions the author offers two complementary theoretical approaches – semiotics and literary sociology. The semiotic approach allows her to accurately identify the communications model according to which Aesopic language functioned and to reveal the risks inherent in it, and also to show how Aesopic language affected society as both a process and an ideological passional structure. The sociological approach leads her to explore the role of Aesopic language within the literary field, to discuss some of that field’s actors’ positions and tendencies, and to consider how self-censorship functions in the case of Aesopic language and how it inserts itself into the habitus of that field’s actor. This attempt to conceptualize Aesopic language opens a path to considerations about the history of Lithuanian literature of the Soviet period.
Keywords: Aesopic language; poetics; semiotics; literary sociology; literary field; communications model; censorship